Sosialisasi Pentingnya Implementasi Manajemen Risiko, ISO 14001 dan ISO 45001 - Lulus Suci Hendrawati; Agung Cahyono; Yunita Sari Purba (Jurnal Pengabdian Masyarakat Bakti Parahita, 2023)
Risk management (risk management) is a process of planning, organizing, leading, and controlling the activities of an organization to minimize the risk of the company's income. One of the implementations of the occupational health and safety management system are about the implementation of ISO 14001 and ISO 45001. The socialization of the implementation of risk management, ISO 18001 and ISO 45001 is expected to increase awareness of worker behavior in implementing OHSMS at PT. APJ. This increase in knowledge about OHSMS is already in accordance with several research result. One of the results of the study shows, that there is an effect of knowledge on worker behavior. Worker behavior also influences the incidence of work accidents. This is a strong reason for creating a OHS knowledge improvement program. Good knowledge about OHS will also be able to increase good safety behavior. Counseling is one of the knowledge improvement programs carried out by PT. APJ. The results of the counseling obtained an increase in good knowledge of HSE staff and Supervisors of PT. APJ from 27.2% to 56.8%.